Anticancer effect of 2, 7-dihydroxy-3-methylanthraquinone on human gastric cancer SGC-7901 cells in vitro and in vivo. (1st February 2016) - Zhu, Haitao; Zheng, Zhichao; Zhang, Jianjun; Liu, Xiaoping; Liu, Yang; Yang, Wei; Liu, Yong; Zhang, Tao; Zhao, Yan; Liu, Yanqing; Su, Xiaohui; Gu, Xiaohu
Abstract: Context : 2, 7-Dihydroxy-3-methylanthraquinone (DDMN) is reported to have a remarkable anticancer activity against gastric cancer SGC-7901 cells. Objective : The objective of this study is to study the anticancer effect and mechanism of DDMN on SGC-7901 cells. Materials and methods : The MTT assay was used to determine the effect of DDMN on cell viability of SGC-7901 cells, and the cytotoxic effect was evaluated by the IC50 value. After treatment with different doses of DDMN (10, 20, and 40 μM) for 48 h, flow cytometry was used to investigate the apoptosis of SGC-7901 cells induced by DDMN. Further, western blotting was performed to study anticancer mechanism by assaying apoptosis-related proteins containing Mcl-1, Bcl-xl, Bcl-2, Bax, Bak, Bad, cytochrome c, caspase-3, and caspase-9. Finally, xenograft assay was used to further evaluate the effect of DDMN on SGC-7901 cells by determining body weight of nude mice, tumor volumes, and apoptosis-related proteins. Results : These results suggest that DDMN can significantly inhibit (IC50 value = 20.92 μM) the proliferation of SGC-7901 cells and induce apoptosis of SGC-7901 cells demonstrated by flow cytometry analysis. Additionally, the results of western blotting indicated that DDMN can suppress the expression of anti-apoptotic proteins Bcl-xl and Bcl-2, increase the expression of pro-apoptotic proteins Bax, Bad (40 μM), caspase-3 and caspase-9, and evidently promote the release of cytochrome c from the mitochondria to the cytoplasm. The xenograft assay further confirmed that DDMN had significant anticancer effects on SGC-7901 cells. Conclusion : DDMN had significant anticancer effect on SGC-7901 cells in vitro and in vivo related to mitochondria-mediated apoptosis.